2007
DOI: 10.1063/1.2715474
|View full text |Cite
|
Sign up to set email alerts
|

The fabrication and characterization of (Pb,Ca)TiO3 pyroelectric thin films with different Ca contents

Abstract: This study uses radio-frequency sputtering methods to deposit lead titanate thin films with different contents of Ca on Pt∕Ti∕SiO2∕Si substrates to form Pb1−xCaxTiO3 (PCT) thin films. The PCT thin films contained different amounts of Ca in order to examine the influence of the Ca content on the properties of thin films. Analysis of the electrical properties of the PCT thin films revealed that their relative permittivities, dissipation factors, and pyroelectric coefficients tend to increase with the Ca content.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Ye et al [16] reported pyroelectric PZT film that was deposited by sol-gel method on p-Si substrate and annealed at 400°C showed a pyroelectric coefficient 50-80 Â 10 À5 C/m 2 K at room temperature. Chang et al [17] showed pyroelectric coefficient of 15 Â 10 À5 C/m 2 K for PCT film that was sputtered on Pt surface and annealed at 650°C. Chopra et al [18] also reported high pyroelectric coefficient of PCT film (433 Â 10 À5 C/m 2 K) that was grown by sol-gel method on ITO surface.…”
Section: Pyroelectric Current Measurements After Polingmentioning
confidence: 99%
“…Ye et al [16] reported pyroelectric PZT film that was deposited by sol-gel method on p-Si substrate and annealed at 400°C showed a pyroelectric coefficient 50-80 Â 10 À5 C/m 2 K at room temperature. Chang et al [17] showed pyroelectric coefficient of 15 Â 10 À5 C/m 2 K for PCT film that was sputtered on Pt surface and annealed at 650°C. Chopra et al [18] also reported high pyroelectric coefficient of PCT film (433 Â 10 À5 C/m 2 K) that was grown by sol-gel method on ITO surface.…”
Section: Pyroelectric Current Measurements After Polingmentioning
confidence: 99%
“…All of the characteristic peaks of PZT, especially the (110) peak, become much stronger and sharper as the annealing temperature increases. The full width at half-maximum (FWHM) is considered in evaluating the quality of the PZT thin film [23,24]. Figure 1(b) indicates the FWHM of the perovskite phase peak (110) as a function of the annealing temperature.…”
Section: Crystalline Phase Of Pzt Thin Filmmentioning
confidence: 99%
“…It has been shown to have a high pyroelectric figure of merit and is considered to be a very good candidate for thin film pyroelectric detector [14,15]. A 30% Ca content was found to deliver the best pyroelectric detector behavior [15]. The addition of Ca decreased the dielectric constant while maintaining relatively the same pyroelectric constant.…”
Section: ∆P=γ∆tmentioning
confidence: 98%
“…Calcium modified lead titanate has received some attention as pyroelectric material because of its better mechanical stability and enhanced sensing properties [13]. It has been shown to have a high pyroelectric figure of merit and is considered to be a very good candidate for thin film pyroelectric detector [14,15]. A 30% Ca content was found to deliver the best pyroelectric detector behavior [15].…”
Section: ∆P=γ∆tmentioning
confidence: 98%